2020
DOI: 10.1371/journal.pntd.0008059
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Anopheles mosquitoes to trypanosomes reduces reproductive fitness and enhances susceptibility to Plasmodium

Abstract: During a blood meal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In African mosquitoes (Anopheles coluzzii) that become infected with trypanosomes, Trypanosoma brucei, qPCR revealed a five-fold increase in the total enteric bacterial population within two days after infection and again after a blood meal. The effects were similar regardless of the blood source [66]. The intensity of Plasmodium infection in its mosquito host also may be directly correlated with the abundance of midgut Enterobacteriaceae populations.…”
Section: How Do the Microbial Symbionts Affect Vector Health And Reproduction And Contribute To Fitness Of The Vector Host?mentioning
confidence: 79%
“…In African mosquitoes (Anopheles coluzzii) that become infected with trypanosomes, Trypanosoma brucei, qPCR revealed a five-fold increase in the total enteric bacterial population within two days after infection and again after a blood meal. The effects were similar regardless of the blood source [66]. The intensity of Plasmodium infection in its mosquito host also may be directly correlated with the abundance of midgut Enterobacteriaceae populations.…”
Section: How Do the Microbial Symbionts Affect Vector Health And Reproduction And Contribute To Fitness Of The Vector Host?mentioning
confidence: 79%
“…Yet, the organism displays the hallmarks of a parasitic infection as oocysts are ingested from the larval water, enter epithelial cells, and use host cell mitochondria to supply the energy required to mature ( Chen and Wu, 1997 ). Trypanosoma brucei , a protist parasite and causative agent of trypanosomiases, normally carried by tsetse flies, can survive in mosquito midguts for up to 48 h. Co-infection of mosquitoes with Trypanosoma and Plasmodium increased the malarial parasite load in the mosquito, potentially increasing the risk of malarial spread ( Dieme et al, 2020 ). Thus, there is evidence that the microbiome of the mosquito may host a population of protists, but their roles and interactions with the host are essentially undescribed.…”
Section: A Path Forward: a Most Wanted List For Microbes In Gnotobiotic Studiesmentioning
confidence: 99%
“…Instead, our findings may suggest a second model in which sensing pathogen infection leads to the induction of genes that play a role in surveillance and resistance to possible coinfecting pathogens. Coinfections are commonly observed in natural populations of various species [9395]. It has been demonstrated that coinfection can lead to decreased host resistance in nature and laboratory experiments [9597], and negatively impact host health [94, 98].…”
Section: Discussionmentioning
confidence: 99%
“…Coinfections are commonly observed in natural populations of various species [9395]. It has been demonstrated that coinfection can lead to decreased host resistance in nature and laboratory experiments [9597], and negatively impact host health [94, 98]. These previous findings suggest that avoidance of coinfection would increase host fitness, and support a model in which infection by any pathogen may provoke a generalized prophylactic response against coinfection alongside the specific response to the primary pathogen.…”
Section: Discussionmentioning
confidence: 99%